Geochemistry of Tertiary Sequence in Shahbajpur-1 Well, Hatia Trough, Bengal Basin, Bangladesh: Provenance, Source Weathering and Province Affinity (Journal of Life and Earth Science, 2014)
Major and trace element compositions of Neogene sandstones and mudrocks from the Shahbajpur-1 (SB-1) well, Hatia trough, Bengal basin, Bangladesh were determined to examine their geochemical characteristics and provenance, in relation to Himalayan uplift, sediment dispersal, and correlation of coeval successions in a basinal context. Major and trace element abundances in the SB-1 succession vary vertically, with SiO2 content decreasing and Al2O3 increasing from the older (Surma and Tipam Groups) to younger (Dupi Tila Group) sediments. Marked geochemical fractionation between sandstones and mudrocks reflects advanced hydrodynamic sorting, and relative enrichment of several elements (e.g., TiO2, Zr, Ce, Th, Cr) suggests sporadic heavy mineral concentration in some sandstones. Major and trace element provenance discriminants indicate a uniform felsic source (Himalayan detritus and recycled sediments) for the entire succession. Values for the Chemical Index of Alteration (CIA) record moderate weathering in the source, and non-steady state conditions produced by Himalayan uplift. Comparison between the Hatia trough samples and coeval Sylhet trough (P2) sediments shows that the more distal SB-1 succession is compositionally more uniform. Strong similarity in geochemical composition between SB-1 and P2 support the hypothesis that the Hatia trough is an extension of P2, fed by the same dispersal system. DOI: http://dx.doi.org/10.3329/jles.v7i0.20115 J. Life Earth Sci., Vol. 7: 1-13, 2012